Effect of a mixture of nut residue powder, potato starch and instant dry yeast on the quality of sandwich bread - Duy, Tran Huu; Han, Dang Nguyen Gia; Giau, Tran Ngoc; Hao, Hong Van; Thuy, Nguyen Minh (Journal of Food Technology Research, 2026)
This study employed a combination of nut residue powders (soy, peanut, and cashew) to partially replace wheat flour in a sandwich bread formulation. In the initial trial, the nut residue mixture (NRM) powders, substituting wheat flour at levels ranging from 10% to 17.5%, were coded as G1 through G4, with a control sample G0 containing 100% wheat flour. Subsequently, potato starch (PS) (6% to 10%) was incorporated as a substitute for wheat flour, and instant dry yeast (0.5% to 0.7%) was added to enhance the physical qualities of the final product. Among the four recipes designed for partial wheat flour replacement, the results indicated that bread from Recipe G2, which contained NRM powder and wheat flour in a ratio of 12.5:87.5%, exhibited high specific volume and volume expansion, along with moderate hardness (727.37 and 277.90 grams-force, respectively) and an appealing color. However, the specific volume and volume expansion of G2 bread remained lower than those of the control G0. The subsequent partial replacement of wheat flour with potato starch and the use of quick-dry yeast compensated for this shortcoming. The formulation, referred to as PI, with a ratio of PS:NRM: wheat flour of 7.79:12.5:79.71% and yeast at 0.56%, produced a product with superior structure and higher contents of protein, fat, fiber, ash, and total polyphenols compared to G0. Notably, the fiber content in the PI sample was approximately 3.3 times higher. Additionally, the estimated glycemic index (eGI) of the PI bread was lower at 51.16 compared to 67.6 for G0, indicating a medium-low glycemic response. This research demonstrates the effective utilization of by-products in food processing and suggests potential for further application in the bakery industry or other food sectors where demand exists for healthier and functional products.